Adaptation of Chabot emotional differentiation scale to Turkish language and examination of emotional differentiation levels of married people - Bellur, Esra; Dincyurek, Sibel (Springer, 2022)
This study aims to adapt the Chabot Emotional Differentiation Scale (CED) developed by David Chabot (1993) to the Turkish language and to test its reliability and validity on married individuals in North Cyprus. The study group consists of 433 married individuals. The sample is randomly divided into sample 1 (n = 217) for exploratory factor analysis and sample 2 (n = 216) for confirmatory factor analysis to test the construct validity of the Turkish adapted scale (CED-T). A two-factor structure was obtained from the scale and four items were excluded. One item was excluded from the confirmatory factor analysis and the scale was finalized with 12 items. The study calculated Cronbach Alpha internal consistency coefficients and found reliability coefficients to be sufficient. In addition, it examined the relationship between CED-T scores, trait anxiety scores and married life satisfaction scores, and found that the scale supported the criterion-related validity. The data revealed that CED-T is a valid and reliable measurement tool.
Keywords: Differentiation of self; Emotional differentiation; Trait anxiety; Satisfaction of marriage